2016
DOI: 10.19041/apstract/2016/4-5/17
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Albanian consumer preferences for standardized olive oil

Abstract: Albania is considered one of the most important countries where olives are cultivated due to its geographical position and climate conditions. The country is facing many problems with the quality of olive oil which is related to cultivation methods and agronomic techniques. The economic value of the sector is calculated almost €20 million per year. For years the cultivation of olives and associated products have been considered an important sector within agriculture and are an integral part of the Albanian die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…which together make up 82% of those surveyed. In another research of Muça et al [97], dealing also with Albanian consumers, it was found that they usually develop trust relationships with suppliers because they lack other information about the quality of the olive oil at the time of purchase. Hence, Albanian consumers preferred domestic olive oil, mostly from the south of Albania, because they were familiar with the taste and believe in its qualities not like when olive oil is imported.…”
Section: Consumers Attitudes and Behavior Regarding 'Local' Labeling On Olive Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…which together make up 82% of those surveyed. In another research of Muça et al [97], dealing also with Albanian consumers, it was found that they usually develop trust relationships with suppliers because they lack other information about the quality of the olive oil at the time of purchase. Hence, Albanian consumers preferred domestic olive oil, mostly from the south of Albania, because they were familiar with the taste and believe in its qualities not like when olive oil is imported.…”
Section: Consumers Attitudes and Behavior Regarding 'Local' Labeling On Olive Oilmentioning
confidence: 99%
“…The lack of a clear definition represents an obstacle in the analysis of local food demand [57]. In the case of olive oil, various studies conducting consumer research on olive oil have considered the local attribute as an influencing factor on consumer behavior for olive oil [95][96][97][98][99], but the different perceptions and definitions of the term 'local' among consumers, researchers, regions and policymakers led to a variety of judgments among consumers.…”
Section: Consumers Attitudes and Behavior Regarding 'Local' Labeling On Olive Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, spices have played an important role in economic development as a consistent source of income, employment, and a healthy option in the global food seasoning industry (Jiang, 2019). Global demand for spices remains robust, with the United States of America (USA) being the world's largest market in terms of demand for spices in both consumption and imports (Nguyen et al, 2019). Over the past several years, the spice and herb industries in South Africa have experienced a significant increase in demand (Asowata-Ayodele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%